2009
DOI: 10.2514/1.36547
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir Probe Studies of Magnetic Confinement in an Ion Thruster Discharge Plasma

Abstract: Magnetic confinement studies on a 30-cm-diameter ion thruster were performed to determine the dependence of plasma confinement and uniformity on the ring-cusp magnetic field. Four primary cases were investigated to determine the effects of an additional magnetic cusp, increasing the strength of the highest value closed magnetic contour line, and varying the magnetic field free volume. A laboratory model NASA Solar Electric Propulsion Technology Application Readiness engine was modified to investigate three-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…[15][16][17] The probe I-V characteristic is created by plotting the measured current versus the applied voltage, from which the floating potential V f is determined by finding out the voltage where the net current is zero, and the plasma potential V s is determined by finding out the voltage where the derivative of the I-V characteristic is maximum. The transition region of the I-V characteristic should be a straight line when the probe current is plotted semi-logarithmically versus the probe voltage V p under the assumption that the electrons being measured follow the Maxwellian distribution.…”
Section: A Electron Temperatures Derived From the Classical Single Lmentioning
confidence: 99%
“…[15][16][17] The probe I-V characteristic is created by plotting the measured current versus the applied voltage, from which the floating potential V f is determined by finding out the voltage where the net current is zero, and the plasma potential V s is determined by finding out the voltage where the derivative of the I-V characteristic is maximum. The transition region of the I-V characteristic should be a straight line when the probe current is plotted semi-logarithmically versus the probe voltage V p under the assumption that the electrons being measured follow the Maxwellian distribution.…”
Section: A Electron Temperatures Derived From the Classical Single Lmentioning
confidence: 99%
“…Nominal voltage from throttle table [33] Nominal voltage from throttle table [38] Nominal voltage from throttle table [39] Nominal voltage from throttle table [12] Nominal voltage from throttle table [12] Table A1 Sources of data used to define CEX2D and CEX3D code input parameters (continued) 5 eV for all cases (consistent with Langmuir probe measurements on LM thruster) [40] 5 eV for all cases (consistent with Langmuir probe measurements on LM thruster) [41] 5 eV for all cases (consistent with Langmuir probe measurements on LM thruster) [41] 5 eV for all cases (consistent with Langmuir probe measurements on LM thruster) [41]…”
Section: Beam Voltagementioning
confidence: 80%
“…The upstream plasma potential was assumed to be equal to the sum of the beam voltage and the discharge potential. Emissive probe measurements in NSTAR and NEXT thrusters showed that the plasma potential near the grids was within ±1 V of the discharge voltage [40,41]. The upstream electron temperature was assumed to be 5 eV for all simulations.…”
Section: Input Parameters For the Validation Casesmentioning
confidence: 99%
See 1 more Smart Citation